2011
DOI: 10.1002/j.0022-0337.2011.75.8.tb05146.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental Students’ Attitudes Toward Underserved Populations Across Four Years of Dental School

Abstract: The objective of this study was to assess dental students' attitudes toward underserved populations across their four years of dental school. Students at the Herman Ostrow School of Dentistry of the University of Southern California were invited to take part in the study. Participating students completed a questionnaire on their attitudes toward the underserved at three time points: 1) during orientation week; 2) at the end of their second year after taking part in some community dental programs; and 3) at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
41
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 29 publications
4
41
1
Order By: Relevance
“…Intent to serve at‐risk patients did not appear to change much as the students progressed through dental school. Some prior research indicated a negative effect of dental education and practice on provider attitudes about service to at‐risk populations 22, 30 . In Habibian et al's study, students reported feeling personal responsibility and impact‐potential for treating populations with low income, although their self‐reported capability declined over time 22 .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Intent to serve at‐risk patients did not appear to change much as the students progressed through dental school. Some prior research indicated a negative effect of dental education and practice on provider attitudes about service to at‐risk populations 22, 30 . In Habibian et al's study, students reported feeling personal responsibility and impact‐potential for treating populations with low income, although their self‐reported capability declined over time 22 .…”
Section: Discussionmentioning
confidence: 92%
“…Some prior research indicated a negative effect of dental education and practice on provider attitudes about service to at‐risk populations 22, 30 . In Habibian et al's study, students reported feeling personal responsibility and impact‐potential for treating populations with low income, although their self‐reported capability declined over time 22 . Our study's findings did not indicate such a trend based on advanced class status, but coincided with a general feeling of personal responsibility among these students towards at‐risk populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 On the other hand, dental students' expressions of less positive attitudes towards volunteerism and underserved populations between the irst and fourth years of dental school could be rooted in their growing awareness of such issues and their uncertainty about being able to have a signiicant impact on the reduction of oral health inequities. 24,25 Although there is a body of literature on the beneits of CBDE programs to dental students, there is limited evidence of the type of content delivered to enhance students' knowledge of elements that impact the populations treated and how the students' knowledge of these elements is assessed. In addition, since 2003, 13 new DDS/DMD programs have been established, with nine of those opening between 2010 and 2018.…”
mentioning
confidence: 99%
“…6 Other studies have reported that CBDE improved students' ability to provide care for patients from low-income and underserved populations as well as inluenced their intention to practice in rural settings. [7][8][9][10] However, it is unclear from prior research what speciic elements of these rotations help bring about changes in graduates' values and behavior. For example, is it merely that students are exposed to rural, underserved, and diverse patient populations, or are intentional elements needed to develop these desired value and behavioral changes?…”
mentioning
confidence: 99%